2021
DOI: 10.1016/j.physio.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal manipulative therapy on pain relief and function in patients with chronic low back pain: an individual participant data meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
1
20
3
1
Order By: Relevance
“…SM is the main intervention used by chiropractors for the management of back pain ( 10 , 11 ). Recent meta-analyses including individual participant data indicate that SM may be as effective as other recommended therapies for the management of chronic low back pain ( 12 , 13 ). However, current data does not allow the identification of patients that will benefit more or less from SM therapy ( 14 ), in part because the mechanisms of both low back pain and its relief by SM remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SM is the main intervention used by chiropractors for the management of back pain ( 10 , 11 ). Recent meta-analyses including individual participant data indicate that SM may be as effective as other recommended therapies for the management of chronic low back pain ( 12 , 13 ). However, current data does not allow the identification of patients that will benefit more or less from SM therapy ( 14 ), in part because the mechanisms of both low back pain and its relief by SM remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The data pooled from 47 randomized controlled trials indicated that SMT provides improvements in pain and disability that are similar to those of recommended therapies for the management of chronic LBP, including exercise (60). The analysis of individual participant data from 21 of these trials confirmed these findings while not being able to identify any individual characteristic that could act as a moderator of the benefits provided by SMT (103,104). Therefore, chronic LBP patients may benefit from SMT and exercise to a similar extent, although it is still not possible to determine which treatment approach will be more beneficial for which patients.…”
Section: Effectiveness Of Spinal Manipulative Therapy Compared To Usual Care For Low Back Painmentioning
confidence: 96%
“…A recent meta-analysis by Coulter et al found moderatequality evidence to suggest that SMT significantly reduces pain and disability in patients with chronic LBP compared to both exercise and physical therapy (97). A set of three meta-analyses investigated the effects of SMT in patients with chronic LBP by comparing SMT or mobilization to currently recommended therapies (mainly exercise), non-recommended or ineffective therapies (inactive controls), and a combination of interventions (60,103,104). The data pooled from 47 randomized controlled trials indicated that SMT provides improvements in pain and disability that are similar to those of recommended therapies for the management of chronic LBP, including exercise (60).…”
Section: Effectiveness Of Spinal Manipulative Therapy Compared To Usual Care For Low Back Painmentioning
confidence: 99%
“…Although spinal manipulative therapy has a small immediate effect on the functionality of patients with cLBP (24), there is no speci c patient characteristic that identi es patients more likely to bene t from this intervention (25). Recognising patients' perceptions about the causes of pain and reducing the LBP is essentially better to guide clinical practice and future research (26,27).…”
Section: Introductionmentioning
confidence: 99%